Universitätsmuseen und -sammlungen im Hochschulalltag - Aufgaben, Konzepte, Perspektiven ; Beiträge zum Symposium vom 18.-20. Februar 2010 an der Humboldt-Universität zu Berlin (ums2010) - Weber, Cornelia (Humboldt-Universität zu Berlin, 2011)
Almost every German university owns collections, which are used in teaching and research and/or fulfill the function of a museum. Although they are invaluable in contrast to ordinary museums they distinctly lead a miserable existence. Among museum experts they are therefore called Cinderella Collections. Basically the situation of university museums and collections can be described as deficient if not disastrous. As long as a collection fulfills the purpose, which is attached in teaching and research it is admittedly integrated into the daily routine of the university but is not necessarily promoted and cherished in an appropriate way. Is the original purpose dropped, in the course of the conservation the neglect impends. Many valuable collections have been lost in this way already: through the change of teaching- and research methods, dropping of a subject, closure of a department or measures of reorganization or cost-cutting. Not least the growing and likewise realigning field of science communication, which now also integrates an historical component and the potentially identity-establishing exhibition pieces played a part in contributing to a bigger attention for university collections in the last few years. Nevertheless a critical review shows, that the involved institutions and persons responsible are mostly lacking in the required support, which they need urgently in dealing with these collections. An appropriate indexing and support in a proper way, a better integration in research and teaching as well as initiatives of coordinated science communication - all that has not been traced consequently enough yet. The current situation of university collections, which is absolutely unsatisfactory can be in our opinion only be improved, if persons responsible develop concepts and strategies together, that not only assure the maintenance of academic collections but display them as integrative and identity-lifting elements of the university as well. The establishment of a respective network therefore seemed to be a first, inevitable step. This volume contains contributions to a symposium on this theme, which took place within the funded initiative "research in museums" by support of the "Volkswagen Foundation".